Harlequin’s Tailors: Letters from Iceland by W. H. Auden and Louis MacNeice - Greaves, Sara (Viatica, 2023)
Writing for four hands or more is gaining ground in contemporary academia, including in the humanities where it is still far less the norm than in the sciences, and with the current interest in cross-discipline research, chalk-and-cheese partnerships of all kinds are appearing. In the creative arts and in particular literature, the special status of the singular (in both senses of the word) author continues to command respect – and nowhere more so than in poetry –despite being under attack f.